PERANCANGAN WEDDING CENTER BATAK BOLON DENGAN ARSITEKTUR TRADISIONAL MODERN DI BOGOR - Valiantino Reinhard Martahan; Sri Kurniasih; Karya Subagya (MAESTRO, 2020)
Modern Traditional Architecture that combines traditional architecture and modern architecture., Is applied in the design of the Batak Bolon Wedding Center in Bogor. The large number of Toba Batak youths who have not been married and the lack of wedding hall facilities which are usually used to hold weddings by the Batak tribe in the Bogor area have made these young men get married outside the city of Bogor. So the need for a special Batak wedding building facility in the Bogor area is needed.